Phytochemical and nutritional analyzes of Solanum macrocarpon leaves harvested in Benin - KOUDORO, YAYA ALAIN; AGBANGNAN, DOSSA COKOU PASCAL; BOGNINOU AGBIDINOUKOUN, G. SOPHIE REINE; GBAGAN, Solange; KANFON Rose Estelle, Rose Estelle; AVLESSI, FÉLICIEN; SOHOUNHLOUE, KOKO CODJO DOMINIQUE (My University, 2021)
Vegetables are very important sources of protein and minerals for people. This study aims to promote Solanum macrocarpon on diet in Benin through phytochemical analysis and assessment of nutritional potential its leaves. Ash following standard ISO 749:1977, proteins according to ISO 5983:2005; content of mineral and trace elements by atomic absorption spectrophotometry and secondary metabolites following staining and precipitation reactions specific to each metabolite family. Determination of total phenolic compounds was made by Folin-Ciocalteu reagent. Aluminum trichloride method has been used to quantify total flavonoids, while the determination of condensed tannins was carried out by hydrochloric vanillin method. The results revealed that Solanum macrocarpon leaves contain flavonoids, tannins, proteins and saponosides. The yield of ethanol extract is 19.60%; the ash content is 15.22% and 3759 mg/Kg of proteins. The content of mineral and trace elements showed 428.90 mg/kg of potassium, 31.75 mg/kg phosphorus; 700.25 mg/kg of iron; 6.91 mg/kg of magnesium, 2199.49 mg/kg of sodium, 601.44 mg/kg of nitrogen and 157.10 mg/kg of calcium. These results therefore reflect a high nutritional potential of Solanum macrocarpon leave for people in Benin.
Keywords: Solanum macrocarpon; alkaloids; flavonoids; tannins; proteins and saponosides.